Pengaruh Kepribadian Dan Kemampuan Kerja Terhadap Kinerja Pegawai Pada Kantor Kejaksaan Negeri Raba Bima - Khairunnisah Khairunnisah; Mukhlis Mukhlis (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this research is to determine the influence of personality and work abilities on employee performance at the Raba Bima District Prosecutor's Office. The population in this study was 60 employees. The sample used in this research was 45 employees. The sampling technique used in this research is purposive sampling. Purposive sampling is a technique for determining samples with certain considerations (Sugiyono, 2016). The criteria for respondents in this research are ASN (state civil servants) employees at the Raba Bima District Prosecutor's Office.